Keterlibatan Karyawan sebagai Intervensi Teknostruktural dalam Pengembangan Organisasi: Sebuah Tinjauan Literatur Sistematis - Kartika Safira; Kadek Rahma Sari (Journal of Economics and Management Scienties, 2026)
This study presents a systematic literature review of research on Employee Involvement (EI) as a technostructural intervention within the Organization Development (OD) framework. Drawing on 150 articles published between 2021 and 2026, it maps the conceptual landscape, antecedents, and outcomes of EI interventions. The study employs a Systematic Literature Review (SLR) guided by the PRISMA 2020 protocol. The bibliometric tools used comprise VOSViewer, Publish or Perish (PoP), and Mendeley, with data retrieved from Google Scholar through the Publish or Perish (PoP) application. EI is shaped by four principal antecedent clusters, namely leadership and managerial support, organizational culture and climate, structural and job-design factors, and individual psychological conditions. EI interventions generate outcomes at both the individual and organizational levels. Three dominant forms of EI application are identified: Parallel Structures, High-Involvement Organizations (HIO), and Total Quality Management (TQM). This review addresses a literature gap by offering an up-to-date synthesis of EI research within the technostructural stream of OD, with particular attention to the context of post-pandemic digital transformation and its relevance for organizations in Southeast Asia.